2019
DOI: 10.3390/biom9040133
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenesis of DsbAss is Crucial for the Signal Recognition Particle Mechanism in Escherichia coli: Insights from Molecular Dynamics Simulations

Abstract: The disulfide bond signal sequence (DsbAss) protein is characterized as an important virulence factor in gram-negative bacteria. This study aimed to analyze the “alanine” alteration in the hydrophobic (H) region of DsbAss and to understand the conformational DsbAss alteration(s) inside the fifty-four homolog (Ffh)-binding groove which were revealed to be crucial for translocation of ovine growth hormone (OGH) to the periplasmic space in Escherichia coli via the secretory (Sec) pathway. An experimental design w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 84 publications
(121 reference statements)
1
11
0
Order By: Relevance
“…Molecular docking coupled with MD simulations is an important method to elucidate the mode of interaction of ligands with specific targets, such as enzymes, and to comprehend the enzyme inhibition mechanisms [18,21,23,24,48]. Our in-silico molecular modeling study revealed a favorable binding affinity of linalool and estragole, the two major constituents of this plant, with PPA and PPL ( Figures 6 and 7) and both compounds showed a similar conformation and interactions pattern as reported with their co-crystalized inhibitors.…”
Section: Molecular Modeling Interpretationssupporting
confidence: 63%
See 2 more Smart Citations
“…Molecular docking coupled with MD simulations is an important method to elucidate the mode of interaction of ligands with specific targets, such as enzymes, and to comprehend the enzyme inhibition mechanisms [18,21,23,24,48]. Our in-silico molecular modeling study revealed a favorable binding affinity of linalool and estragole, the two major constituents of this plant, with PPA and PPL ( Figures 6 and 7) and both compounds showed a similar conformation and interactions pattern as reported with their co-crystalized inhibitors.…”
Section: Molecular Modeling Interpretationssupporting
confidence: 63%
“…The AMBER16 simulation package was employed for molecular dynamic simulations which uses the AMBER ff99SB force field [35,36]. The same stepwise energy minimization and equilibration protocol was utilized as described in previous studies [18,21,23,24]. The solvated system with explicit water molecular (TIP3 system) was submitted to a production run of 20ns at constant 300 K temperature and 1 bar pressure.…”
Section: Molecular Docking Analysis and Molecular Dynamics Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The approach is typically based on MD simulations of protein-ligand complexes. It has been applied to numerous systems with varying success (Chen et al, 2016;Durrani et al, 2019;Parveen et al, 2019;Sirin et al, 2014) and better covered in various reviews (Chen et al, 2016;Gohlke & Case, 2004;Gohlke et al, 2003). The AMBER MM-GBSA energetic components for each complex are tabulated in Table 1.…”
Section: Binding Free Energy Calculations With Ambermentioning
confidence: 99%
“…The accessory roles of non-catalytic domains (CBMs) on thermal stability and insoluble substrate degrading efficiencies have been extensively reported by removing or grafting from respective catalytic domain/s [ 17 , 18 , 19 , 20 , 21 , 22 ]. MD simulations (molecular dynamics, is used to analyze physical movements of atoms and molecules by using computational tools) have been used in several studies to evaluate the factors regulating thermostability of enzymes [ 11 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ] and to investigate the stability of the biomolecular complex and interaction attributes [ 31 , 32 ]. These include the thermal stable mechanisms of rubredoxin [ 33 ], nuclease [ 34 ], barnase [ 35 ], nitrile hydratase [ 36 ], adenylate kinase [ 37 ], carbonic anhydrase [ 38 ], carboxylesterase from Geobacillus stearothermophilus [ 39 ], psychrophilic esterase from Pseudoalteromonas haloplanktis [ 40 ], hyperthermophilic esterase from Archaeoglobus fulgidus [ 41 ], thermostable para-nitrobenzyl esterase from Bacillus subtilis [ 42 ], and CBMs from Clostridium cellulovorans [ 43 , 44 ].…”
Section: Introductionmentioning
confidence: 99%